ANTI-OXIDANTS LEVELS IN FEMALE RATS ADMINISTERED PRO-FERTITILITY ETHANOLIC LEAVE EXTRACT OF BYRSOCARPUS COCCINEUS - O. S, Oladimeji; O. A, Lawal; E. O, Ogundimu (European Scientific Journal, ESJ, 2014)
OBJECTIVE: The etiology of female infertility and recurrent pregnancy loss, in some women remains unclear and a scientific challenge. This study was carried out to investigate the qualitative phytochemical analysis, in-vitro and in-vivo antioxidant property of the ethanolic extract of Byrsocarpus coccineus leaves. This was based on the traditional claims, that it is used for the treatment of idiopathic infertility case in females with high body temperature which most times does not favors successful pregnancy. DESIGN: Qualitative phytochemical screening was performed using standard procedures as described by Dipali and Vilas, (2013). In-vitro antioxidant assay of DPPH- 2,2 -Diphenyl-1-picrylhydrazine hydrate radical scavenging activity, Hydrogen Peroxide Scavenging Activity (HPSA) and Total Antioxidant Capacity (TAC) were determined. In-vivo antioxidant activity investigated was catalase (CAT), superoxide dismutase (SOD) and lipid peroxidation. Ethanolic extract of Byrsocarpus coccineus were administered orally for 14 days to the Wister rats in the groups, including female rats induced with temporary infertility with Micronor (MIC) or Nacetylcysteine (NAC) for 7days before the administration of the extract. Results obtained showed that the ethanolic extract of B. coccineus leaves possesses effective antioxidant properties both in-vitro and in-vivo. RESULT / OUTCOME:The phytochemical analysis of the extracts showed the presence of alkaloids, terpenoids, saponins, tannins, flavonoids, resins, phenols and reducing sugars. The extract showed 78.28% inhibition of DPPH, 71.57% of HPSA and 97.95% TAC at 250μg/ml concentrations. Also, the extract significantly causes reduction of the activities of CAT (0.207 ± 0.060 U/ml), SOD (3.83 ± 0.268 U/ml) and lipid peroxidation (1.11 ± 0.027 nmol/ml) compared with control group. The results clearly demonstrated that Byrsocarpus coccineus possess good antioxidant activity as evidenced by the free radical scavenging property in augmenting antioxidant defense mechanisms.